UiTM students’ survey on grocery store - Mohd Zakariah, Izzah Nur Aqilah; Razali, Nurhaziqah Hannani; Khairul Anuar, Norfarah Anina; Abdul Fattah, Qisya Nur Basirah Adawiyah1; Ahmad, Nur Intan Syafinaz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Grocery store refers to a certain category of retail enterprise that concentrates primarily on the distribution of a diverse range of food goods, which can be either fresh or packed depending on the store's particular offerings. Grocery store has a variety of section that sell different categories types of food. Since, grocery store offer more types of food, it is convenient for the students to buy their necessity there but the problem that students have been facing is most of the grocery stores around their campus are out of reach. In fact, several supermarket stores only have one that is close to a university. The grocery store that is conveniently located close to the campus are occasionally sell items at high prices. One of the characteristics that play apart for choosing the grocery store among students is the availability of handy facilities at students' grocery stores, such as parking, mosques, and toilet. Therefore, the purpose of these studies is to determine which grocery stores offer the most satisfying service and facilities. In addition to this, one of our other goals is to identify a supermarket item with a price that is more reasonable than the others. From, the finding it is found that the cheapest grocery store is Mydin. They offer more product at economical price. From the observation Aeon has been chosen as the most convenient facility among other grocery store. In conclusion, different grocery store provide and give different perspective among UiTM students.